The Effect of Leverage, Market Value, and Profitability on Share Prices - Karima, Mutia; Ghazali, Muhammad (SAN Scientific, 2023)
This study analyzes the effect of leverage, market value, and profitability on share prices. This study used a sample of food and beverage industry companies on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique in this study was purposive sampling using 12 companies. The method used in this study is quantitative and uses financial statements data. The research model is multiple linear regression using the SPSS version 25 application. The results of this study are partial. Namely, the DER, PBV, PER, and ROA variables do not affect stock prices. Simultaneously all variables, namely DER, PBV, PER, and ROA, do not affect stock prices. This research is expected not to pay attention to the amount of profit the company alone without knowing the profit capability to generate cash for the company because it is only an illustration of the company's performance in the short term. In addition, investors also need to pay attention to the performance of the company's organizational governance tools to obtain better corporate action information in making investment decisions